A clinicopathological study of perineural invasion and vascular invasion in oral tongue squamous cell carcinoma. Issue 5 (May 2015) - Matsushita, Y.; Yanamoto, S.; Takahashi, H.; Yamada, S.; Naruse, T.; Sakamoto, Y.; Ikeda, H.; Shiraishi, T.; Fujita, S.; Ikeda, T.; Asahina, I.; Umeda, M.
Abstract The risk factors for recurrence of head and neck cancer are classified as being of high or intermediate risk. Those of intermediate risk include multiple positive nodes without extracapsular nodal spread, perineural/vascular invasion, pT3/T4 primary tumours, and positive level IV/V nodes. However, little evidence is available to validate these intermediate risk factors. We analyzed perineural/vascular invasion in 89 patients who underwent radical surgery for oral tongue squamous cell carcinoma, whose records were reviewed retrospectively. Perineural invasion was found in 27.0% of cases and vascular invasion in 23.6%; both had a strong relationship with histopathological nodal status (P = 0.005). The 5-year disease-specific survival (DSS) and overall survival rates of patients with perineural invasion were significantly lower than those of patients without perineural invasion (P < 0.001 and P = 0.002, respectively). The 5-year DSS of UICC stage I and II cases with perineural/vascular invasion was significantly lower than those without (P < 0.001 and P = 0.008, respectively). Perineural invasion and vascular invasion are risk factors for regional metastasis and a poor prognosis. We recommend elective neck dissection when perineural/vascular invasion is found in clinical stage I and II cases. The accumulation of further evidence to consider intermediate risks is required.